EFFICIENT AND SECURE DATA UTILIZATION IN MOBILE EDGE COMPUTING BY DATA REPLICATION - Bhalaji, N. (Journal of ISMAC, 2020)
The technological improvement at a rapid pace in the information and the communication fields has made the internet of things inevitable in our day today activities and takes a significant role in the every part of our regular schedule. The seamless communication through the internet of things is made possible, by connecting the tangible things around resulting in the numerous of advantages such as timely information delivery, servicing and monitoring. The inbuilt benefits of the IOT has made it more prominent among a wide range of application resulting in a huge data flow, though the congestion in the dataflow are managed using the cloud computing and the alternative sources such as the edge computing , the security of the data that are used are still under research. To manage the huge data flow and have secure data utilization in the internet of things, the paper has put forth the mobile edge computing integrated with the data duplication process taking into consideration the power utilization and the response time. The proposed method is simulated using the Network Simulator-2 and results obtained shows that the duplication process provides an enhancement in the bandwidth utilization along with the cut down in the power consumption and the response time.